Lessons from Building Static Analysis Tools at Google. - SADOWSKI, CAITLIN; AFTANDILIAN, EDWARD; EAGLE, ALEX; MILLER-CUSHON, LIAM; JASPAN, CIERA (Communications of the ACM, 2018)
The article discusses the executive of static analysis at the search engine firm Google Inc. Topics include the software development process used by Google, the role of compilers in debugging software at Google, and tools used for workflow integration. Cost-benefit aspects of static analysis are noted.